Topology Optimization of Beam Structures with Various End andLoading Conditions - Woldemichael, Dereje; Jiun, L.; Sujan, D. (Trans Tech Publications, 2014)
Topology optimization deals with optimum material (mass) distribution within a design domain to find optimal lay-out of a structure subjected to certain boundary and loading conditions. Topology optimization can be used to address conflicting requirements, such as light weight and high-strength/stiffness design. In this paper, a simulation program to analyze topology optimization of beam structures with seven different end conditions and three types of loads (single point load, two point loads and uniformly distributed load) is developed using MATLAB code adapted from Sigmund’s 99 line topology optimization code. Furthermore, the program has been enhanced with a graphical user interface for ease of use. Using the developed system, it is possible to analyze the effect of different parameters.